-2(2+x)=7(-3x-1)

Simple and best practice solution for -2(2+x)=7(-3x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(2+x)=7(-3x-1) equation:


Simplifying
-2(2 + x) = 7(-3x + -1)
(2 * -2 + x * -2) = 7(-3x + -1)
(-4 + -2x) = 7(-3x + -1)

Reorder the terms:
-4 + -2x = 7(-1 + -3x)
-4 + -2x = (-1 * 7 + -3x * 7)
-4 + -2x = (-7 + -21x)

Solving
-4 + -2x = -7 + -21x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '21x' to each side of the equation.
-4 + -2x + 21x = -7 + -21x + 21x

Combine like terms: -2x + 21x = 19x
-4 + 19x = -7 + -21x + 21x

Combine like terms: -21x + 21x = 0
-4 + 19x = -7 + 0
-4 + 19x = -7

Add '4' to each side of the equation.
-4 + 4 + 19x = -7 + 4

Combine like terms: -4 + 4 = 0
0 + 19x = -7 + 4
19x = -7 + 4

Combine like terms: -7 + 4 = -3
19x = -3

Divide each side by '19'.
x = -0.1578947368

Simplifying
x = -0.1578947368

See similar equations:

| -25+10c^2=c^2 | | 3x+2.6=x+24 | | 5+6(-1)= | | 2h^2-7h-1= | | 15x-6.3=0 | | g^2+3g= | | 4t^2+8t= | | -7(x-1)=-4(x+7) | | -2x+7=9x+3 | | 5+6z= | | x/5=17 | | .25(y-b)=m | | 3t+5=-15 | | 5-2x=3+3x-4x | | 8x+10-(2x+5)=-55 | | -2(m-60)=-m | | 5m=3m+6 | | 9x=2x^2-18 | | 8x-12=15x+10 | | 6x+12=-6 | | 4+p^2+12p=0 | | 2(x-3)=x+9 | | X^2+7x-38=0 | | x^2+50x+336=0 | | 4x+12=-2(x-3) | | -3(2x-1)=4-3x | | x^2-8x-1008=0 | | s-31=20.6 | | 6x+2=8x-2 | | x^2-4x-320=0 | | 7.2+c=19 | | 25(y+1)-x^2(y+1)= |

Equations solver categories